Principals’ Beliefs About Language Learning and Inclusion of English Language Learners in Canadian Elementary French Immersion Programs - Mady, Callie; Masson, Mimi (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2018)
Gatekeepers’ language ideologies and beliefs about language learning determine how learners experience French as a second language programs, in particular, their access to, and success and inclusion in, the French immersion (FI) program. In this article, we explore how FI principals understand language learning and the inclusion of English language learners (ELLs) and how these perspectives shape school policy in FI programs. The study took place in a large urban school board in southern Ontario with student population consisting of 50% ELLs. After conducting a questionnaire with principals across the school board, we interviewed a subgroup of principals gathering quantitative and qualitative data. In addition, we consulted the board’s website and documentation provided to parents regarding enrolling their children in FI. The study highlights convergence or divergence from principals’ beliefs in relation to board policy about access and inclusion to the FI program. Through critical discourse analysis, data revealed that principals have contradictory beliefs about language learning, and at times principals struggle to reconcile these beliefs with official board policy. While FI principals are mostly positive about including ELLs in FI, to provide equal access to the program, they would benefit from (a) moving away from a definition of bilingualism as equalingualism and (b) expanding and developing the meaning of inclusivity beyond physical presence to adapt the FI space for greater inclusion of ELLs.